Evaluation Visitor Satisfaction and Performance Ecotourism Facilities Management In Manusela National Park - Latupapua, Yosevita Th. (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study aims to assess the level of satisfaction of foreign tourists with interest in bird-watching based on attractiveness opportunities as the main capital for development and improvement for TNM hall managers through indicators of satisfaction expected by visitors. Research data was collected from October to November 2022. It uses a Likert scale to assess visitor perceptions by assessing 47 ecotourism sub-indicators. The research uses the CSI method to determine the level of visitor satisfaction, then uses the IPA method to map the relationship between interests and the performance of 4 indicators: eco-tourism facilities, services, biological resources, and visitor management. The IPA analysis in the Cartesian diagram shows fifteen low-performance indicators, which are the main priorities that must be managed, so the performance of the indicators in this quadrant must be improved with indicators of the availability of signposts, availability of trash cans, clean water networks built above ground level, speed of serving guests arrival, number of guides, competence, quick response, ability, the slope of the land, used for toilets, natural sounds, natural freshness, the distance between activity groups, following regulations. The management of bird-watching at the Masihulan TNM Resort will be harmonized according to laws, regulations, and standard provisions that correlate with eco-tourism management. The conclusion obtained in this research is that the performance quality of bird watching ecotourism management related to infrastructure for visitors has not fulfilled the needs and desires of ecotourists....